Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1089/hum.2017.097
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Bone Repair Using Human Cells: Superior Osteogenic Potential ofBone Morphogenetic Protein 2–Transduced Mesenchymal Stem Cells Derived from Adipose Tissue Compared to Bone Marrow

Abstract: Ex vivo regional gene therapy strategies using animal mesenchymal stem cells genetically modified to overexpress osteoinductive growth factors have been successfully used in a variety of animal models to induce both heterotopic and orthotopic bone formation. However, in order to adapt regional gene therapy for clinical applications, it is essential to assess the osteogenic capacity of transduced human cells and choose the cell type that demonstrates the best clinical potential. Bone-marrow stem cells (BMSC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…However, these hDPSCs are screened from a stromal vascular dental pulp fraction; therefore, this represents a limited source for further research and application. Since ADSCs can be routinely isolated from lipoaspirate with a high degree of purity with minimal donor site morbidity or patient discomfort, ADSCs are considered to have the most significant potential as a primary source for clinical bone tissue engineering [48,56,57]. Additional comparative and screening studies are necessary to identify other cell sources with applications in bone reconstruction.…”
Section: Msc-based Regenerative Medicinementioning
confidence: 99%
“…However, these hDPSCs are screened from a stromal vascular dental pulp fraction; therefore, this represents a limited source for further research and application. Since ADSCs can be routinely isolated from lipoaspirate with a high degree of purity with minimal donor site morbidity or patient discomfort, ADSCs are considered to have the most significant potential as a primary source for clinical bone tissue engineering [48,56,57]. Additional comparative and screening studies are necessary to identify other cell sources with applications in bone reconstruction.…”
Section: Msc-based Regenerative Medicinementioning
confidence: 99%
“…Owing to their ability to differentiate into chondrocytes, MSCs have also been evaluated in the context of cartilage repair [ 33 ]. BM-MSCs, AD-MSCs but also synovium-derived MSCs (S-MSCs) [ 53 ] have been broadly studied in this context [ 53 , 54 ]. While BM-MSCs have shown the best results in terms of chondrogenic differentiation both in vitro and in vivo; S-MSCs have demonstrated enhanced proliferation [ 33 , 53 ].…”
Section: Origin and Relevance Of Mscsmentioning
confidence: 99%
“…These data suggested that hUSCs have the potential to differentiate into osteoblasts. BMP2 is a major member of the BMP family which exhibits strong osteoinductive ability and can induce osteogenic differentiation of adult stem cells such as bone marrow mesenchymal stem cells (BMSCs), adipose mesenchymal stem cells, embryonic stem cells, gingival mesenchymal stem cells, and periodontal ligament stem cells (Bougioukli et al, 2018;Ghaderi et al, 2018;Miao et al, 2018). However, the effects of BMP2 on osteogenic induction of hUSCs have not been reported and the underlying mechanism deserves further exploration to meet the requirements of seed cells for bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%